2022
DOI: 10.3390/genes13020297
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles of Non-Coding RNAs in the Feed Efficiency of Livestock Species

Abstract: A global population of already more than seven billion people has led to an increased demand for food and water, and especially the demand for meat. Moreover, the cost of feed used in animal production has also increased dramatically, which requires animal breeders to find alternatives to reduce feed consumption. Understanding the biology underlying feed efficiency (FE) allows for a better selection of feed-efficient animals. Non-coding RNAs (ncRNAs), especially micro RNAs (miRNAs) and long non-coding RNAs (ln… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 185 publications
(227 reference statements)
0
8
0
5
Order By: Relevance
“…In pigs, the advancement of genomic technologies has enabled researchers to perform different GWAS studies to identify genomic regions and candidate genes associated with economically important traits, including meat quality and quantity, reproductive traits, and FE traits. To date, 34,342 QTLs for 708 different traits have been mapped in the pig genome ( Hu G et al, 2022 ). Taking different FE indicators into account, 410 QTLs for FCR, 96 QTLs for RFI, 143 QTLs for DFI, and 815 QTLs for ADG presented in the animal QTL database by December 2021 ( Hu G et al, 2022 ).…”
Section: Genomics Of Feed Efficiencymentioning
confidence: 99%
See 2 more Smart Citations
“…In pigs, the advancement of genomic technologies has enabled researchers to perform different GWAS studies to identify genomic regions and candidate genes associated with economically important traits, including meat quality and quantity, reproductive traits, and FE traits. To date, 34,342 QTLs for 708 different traits have been mapped in the pig genome ( Hu G et al, 2022 ). Taking different FE indicators into account, 410 QTLs for FCR, 96 QTLs for RFI, 143 QTLs for DFI, and 815 QTLs for ADG presented in the animal QTL database by December 2021 ( Hu G et al, 2022 ).…”
Section: Genomics Of Feed Efficiencymentioning
confidence: 99%
“…To date, 34,342 QTLs for 708 different traits have been mapped in the pig genome ( Hu G et al, 2022 ). Taking different FE indicators into account, 410 QTLs for FCR, 96 QTLs for RFI, 143 QTLs for DFI, and 815 QTLs for ADG presented in the animal QTL database by December 2021 ( Hu G et al, 2022 ). The descriptive information of GWAS studies for FE traits in pigs is shown in Supplementary Table S2 .…”
Section: Genomics Of Feed Efficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that IGF1 gene up-regulation in muscle tissue of Kermani lamb fed with fennel in the diet significantly had greater femur muscle weight, back muscle weight, lean meat weight, final weight, warm carcass weight, and live daily gain than the control one (Shahsavari et al, 2021). In a review study, Hu et al (2022) provided a list of ovine micro RNAs that regulate IGF2, MEF2C, MYEF2, and RB1, which are associated with skeletal muscle differentiation, myelin expression, myogenic differentiation, and proliferation of skeletal muscle sheep F I G U R E 5 The ovine micro RNAs that regulate IGF2, MEF2C, MYEF2, and RB1, which were associated with muscle traits in sheep (retrieved from Hu et al, 2022) satellite cells 5). c.654G>A nucleotide subin exon 3 of the IGF1R gene traits was also reported essential for growth, body size, slaughter, and meat quality in the Colored Polish Merino sheep breed (Grochowska et al, 2020).…”
Section: Ot H Er I M Porta N T Ca N Di Dat E Ge N E S W I T H Po Si T...mentioning
confidence: 99%
“…The ovine micro RNAs that regulate IGF2 , MEF2C , MYEF2 , and RB1 , which were associated with muscle traits in sheep (retrieved from Hu et al, 2022)…”
Section: Other Important Candidate Genes With Positional and Function...mentioning
confidence: 99%